Continued versus interrupted targeted therapy during metastasis-directed stereotactic radiotherapy: a retrospective multi-center safety and efficacy analysis - Kroeze, Stephanie; Fritz, Corinna; Schaule, Jana; Blanck, Oliver; Kahl, Klaus-Henning; Kaul, David; Siva, Shankar; Gerum, Sabine; Claes, An; Sundahl, Nora; Adebahr, Sonja; Stera, Susanne; et al. (Cancers, 2021)
The increasing use of targeted therapy (TT) has resulted in prolonged disease control and survival in many metastatic cancers. In parallel, stereotactic radiotherapy (SRT) is increasingly performed in patients receiving TT to obtain a durable control of resistant metastases, and thereby to prolong the time to disseminated disease progression and switch of systemic therapy. The aims of this study were to analyze the safety and efficacy of SRT combined with TT in metastatic cancer patients and to assess the influence of continuous vs. interrupted TT during metastasis-directed SRT. The data of 454 SRTs in 158 patients from the international multicenter database (TOaSTT) on metastatic cancer patients treated with SRT and concurrent TT (within 30 days) were analyzed using Kaplan-Meier and log rank testing. Toxicity was defined by the CTCAE v4.03 criteria. The median FU was 19.9 mo (range 1-102 mo); 1y OS, PFS and LC were 59%, 24% and 84%, respectively. Median TTS was 25.5 mo (95% CI 11-40). TT was started before SRT in 77% of patients. TT was interrupted during SRT in 44% of patients, with a median interruption of 7 (range 1-42) days. There was no significant difference in OS or PFS whether TT was temporarily interrupted during SRT or not. Any-grade acute and late SRT-related toxicity occurred in 63 (40%) and 52 (33%) patients, respectively. The highest toxicity rates were observed for the combination of SRT and EGFRi or BRAF/MEKi, and any-grade toxicity was significantly increased when EGFRi (p = 0.016) or BRAF/MEKi (p = 0.009) were continued during SRT. Severe (≥grade 3) acute and late SRT-related toxicity were observed in 5 (3%) and 7 (4%) patients, respectively, most frequently in patients treated with EGFRi or BRAF/MEKi and in the intracranial cohort. There was no significant difference in severe toxicity whether TT was interrupted before and after SRT or not. In conclusion, SRT and continuous vs. interrupted TT in metastatic cancer patients did not influence OS or PFS. Overall, severe toxicity of combined treatment was rare; a potentially increased toxicity after SRT and continuous treatment with EGFR inhibitors or BRAF(±MEK) inhibitors requires further evaluation.
Gesehen am 29.01.2022